Temporary and permanent migrant selection: Theory and evidence of ability‐search cost dynamics - Chen, Joyce J.; Kosec, Katrina; Mueller, Valerie (John Wiley & Sons, 2019)
We integrate two workhorses of the labor literature, the Roy and search models, to illustrate the implications of migration duration—specifically, whether it is temporary or permanent—for patterns of selection. Consistent with our stylized model, we show that temporary migrants are intermediately selected on education, with weaker selection on cognitive ability. In contrast, permanent migration is associated with strong positive selection on both education and ability, as it involves finer employee–employer matching and offers greater returns to experience. Networks are also more valuable for permanent migration, where search costs are higher. Labor market frictions explain observed network–skill interactions.